PENGEMBANGAN ALAT PERAGA TIMBANGAN UNTUK MENGOPTIMALKAN BELAJAR HITUNG BAGI SISWA SD - Miyarso, Estu (MAJALAH ILMIAH PEMBELAJARAN, 2011)
This study aims to develop visual aids to learn the scales in order to optimize the operation count in elementary students. Knowing the various aspects of learning that can be optimized in low-grade elementary school students through the use of props scales. This study uses a model of development research. Test subjects from this study amounted to 35 people. Types of instruments used in this study were questionnaires, record sheets and the use of development processes, as well as digital photo cameras. The results showed that this research has successfully developed products props scales with the level of airworthiness of products, including the criteria either. Aspects of learning that can be optimized in low-grade elementary school students through the use of props this is the aspect of cognitive scales; of understanding of simple arithmetic operations for addition, subtraction, multiplication, and division is simple with the system converges or diverges mindset. Keywords: Viewer Tool Development Scales, Learning Operations Calculate elementary school children